Widely 70-nm wavelength tunability single-frequency erbium laser utilizing multiple-ring architecture. (December 2019) - Yeh, Chien-Hung; Xie, Yue-Ru; Luo, Chien-Ming; Chang, Yao-Jen
Highlights: Stable single-longitudinal-mode erbium-doped fiber multiple-ring laser is designed. Using C-band EDF gain medium of proposed laser scheme can achieve C + L bands tuning range. The 3 dB Lorentzian linewidth of 14.9 to 20.4 kHz is attained. Abstract: In this paper, to accomplish the broadly wavelength tunability and single-longitudinal-mode (SLM) operation of erbium-doped fiber (EDF) based laser, the multiple-ring structure is designed and executed. The output power of −7.3 to 5.1 dBm and optical signal to noise ratio (OSNR) of 31.5 to 36.7 dB/0.06 nm are obtained for the proposed EDF laser over the tuning range of 1520.0–1590.0 nm based on the C-band EDF gain medium. In addition, the Lorentzian linewidth of 14.9 to 20.4 kHz is also attained.